2008
DOI: 10.2167/cit335.0
|View full text |Cite
|
Sign up to set email alerts
|

Slaughtering the Goose that Lays the Golden Egg: Are Whaling and Whale-Watching Mutually Exclusive?

Abstract: Tourism interests usually coexist in a delicate balance with other human interests (e.g. residential development and recreational interests) and activities (e.g. fishing, forestry and mining). Such interests and activities may be compatible or incompatible with tourism to varying degrees. Where incompatibility arises it must be carefully managed through compromise, spatial segregation or exclusivity. Conflicting interests between whale-watching and whaling is one topical such case. Events in recent years, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Previous studies have investigated this issue (e.g. Parsons & Rawles, 2003; Cunningham et al ., 2012), but there are very few that have examined how whale-watch tourists may react if whaling occurs in their preferred whale-watching destination (Higham & Lusseau, 2007; 2008). Investigating the cultural and environmental values of this demographic may facilitate an understanding of the degree to which they will partake in whale-watching, in whaling nations (Higham & Lusseau, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated this issue (e.g. Parsons & Rawles, 2003; Cunningham et al ., 2012), but there are very few that have examined how whale-watch tourists may react if whaling occurs in their preferred whale-watching destination (Higham & Lusseau, 2007; 2008). Investigating the cultural and environmental values of this demographic may facilitate an understanding of the degree to which they will partake in whale-watching, in whaling nations (Higham & Lusseau, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst some supporters of whaling believe that it is possible for commercial whaling and whale-watching to co–exist, thereby providing two sources of revenue (Moyle & Evans, 2008), several studies have suggested that the coexistence of these two industries is not feasible (Orams, 2001; Higham & Lusseau, 2008). As well as reducing whale populations overall, whaling can impact upon the local whale populations which support many whale-watching industries, for example by potentially causing whales to develop avoidance responses to boats (Hoyt & Hvenegaard, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For those forms of wildlife tourism that include the possibility of feeding wild animals, other problems can arise, including impaired health and higher levels of aggression toward humans (Burns & Howard, 2003;Orams, 2002;Smith, Samuels, & Bradley, 2008). Negative effects can also occur due to conflicts among stakeholders, for example in the case of whale-watching tourism and traditional economic activities that are based on the same resources, in particular fishery and whaling (Higham & Lusseau, 2008;Parsons & Draheim, 2009). It has been observed that tourism, wildlife tourism included, can lead to negative effects on the local socio-cultural context, and, more generally, on the quality of life of the local communities (Mathieson & Wall, 1982b;Scheyvens, 1999).…”
Section: Wildlife Tourism and Ecotourism: Definitions And Impactsmentioning
confidence: 99%
“…Indeed, whale watching in countries that are still actively hunting whales is arguably more lucrative than whaling [5][6][7]. Statements from politicians in whaling countries claim that whaling and whale-watching can coexist without impacting each other (e.g., [8][9][10][11][12]), but data suggest that whaling can inhibit whale-watching development or potentially reduce whale watching tourism revenues within a country [6,7,[13][14][15]. Whaling may even reduce tourism revenues in general, because of ethical boycotts of whaling locations by tourists [16].…”
Section: Introductionmentioning
confidence: 99%